Cumulative Autoimmunity: T Cell Clones Recognizing Several Self-Epitopes Exhibit Enhanced Pathogenicity - LIBLAU, Roland S. (Frontiers in Immunology, 2011)
T cell receptor (TCR) recognition is intrinsically polyspecific. In the field of autoimmunity, recognition of both self- and microbial peptides by a single TCR has led to the concept of molecular mimicry. However, findings made by our group and others clearly demonstrate that a given TCR can also recognize multiple distinct self-peptides. Based on our data we postulate that recognition of several self-peptides is an important parameter governing the pathogenicity of an autoreactive T cell, and refer to this function as ‘cumulative autoimmunity’. The mechanisms of such increased pathogenicity, and the implications of cumulative autoimmunity regarding the pathophysiology of T cell-mediated autoimmune diseases will be discussed.